Neuroprotective Efficacy of β-caryophyllene on Cerebellar Changes Caused by Bisphenol A in Rats via Alleviating Oxidative Stress - Ahmad Yahyazadeh; Fatih Mehmet Gür; Hatice Yaren Kuloğlu (Turkish Journal of Agriculture: Food Science and Technology)
Exposure to bisphenol A (BP), an environmental pollutant, is potentially harmful to both human health and the environment. The purpose of the current research was to evaluate the effectiveness of β-caryophyllene (CF) (200 mg/kg) on rat cerebellar tissues exposed to BP (250 mg/kg). Thirty-five randomly selected male rats were split into five groups as: control (CON), olive oil (OL), BP, CF, and CF+BP. On day 15 of the experiment, all rats' cerebellar tissues were immediately extracted, followed by stereological and histological examination. Our results revealed that MDA level was significantly elevated in the BP group compared to the CON group (p<0.05). While no significant difference was detected in the mean cerebellar volume among the experimental groups, the BP group’s the Purkinje cell number was significantly reduced when compared to the CON group (p<0.05). In the CF+BP group, we found a significantly lower level of MDA and higher number of Purkinje cells compared to the BP group (p<0.05). Histopathological examination revealed that the BP group had the marked neuronal deterioration; however, in the CF+BP group, this structural alteration was not as severe than the BP group. Our findings showed that exposure to BP caused oxidative damage to cerebellar tissues, and administration of CF attenuated BP-induced toxicity via improvement of oxidative stress.